Utilization of Software for Employee Working Time Efficiency and Accuracy of Coal Reserve Calculation - Denny Boy Sitanggang; I Dewa Ketut Kerta Widana; Dewi Puspaningtyas Faeni (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Digital transformation in the mining sector has increasingly encouraged the adoption of specialized software to improve operational performance, particularly workforce time efficiency and the precision of technical calculations. Objective: This study aimed to evaluate the effect of mining software utilization on employee working time efficiency and the accuracy of coal reserve calculations, addressing a research gap in systematically examining these relationships within open-pit mining operations. Methods: This study employed an integrated quantitative–qualitative approach using a comparative method between manual work processes and software-based processes. The analysis used geological data, topographic data, and mining technical parameters from open-pit mining operations. Data processing was conducted using MineScape to simulate mine planning and reserve estimation, and the results were compared with those obtained through previously used conventional methods. Results: The results indicated that software utilization significantly reduced job completion time and improved the consistency and accuracy of reserve calculation results. In addition, more systematic data integration through software helped minimize potential calculation errors and accelerate the decision-making process. Conclusion: This study concluded that the utilization of mining software had a positive impact on improving work efficiency and the accuracy of coal reserve calculations. Therefore, the implementation of software-based technology is considered a relevant strategy for supporting performance optimization and competitiveness in the mining industry in the digital era.